A Double-blind, Placebo-controlled, Randomized, Multi-centre, Phase III Study of MLC901 (NeuroAiD™II) for the Treatment of Cognitive Impairment After Mild Traumatic Brain Injury - Pilipenko, PI; Ivanova, AA; Kotsiubinskaya, YV; Grigoryeva, VN; Khrulev, AY; Skorokhodov, AV; Gavrik, MM; Mkrtchan, NN; Majdan, M; Valkovic, P; Rabarova, D; Barker-Collo, S; et al. (Public Library of Science (PLoS), 2025)
Introduction About half of the world population will suffer from a traumatic brain injury (TBI) during their lifetime, of which about 90% of cases are mild TBI. Although up to 40% of adults with mild TBI experience persistent functional deficits, there is no proven-effective treatment to facilitate recovery after it. Methods and analysis This randomized placebo-controlled multi-centre study was aimed to examine the efficacy of herbal supplement MLC901 on complex attention following mild TBI at 6 months post-randomisation, as a primary outcome measured by CNS Vital signs (CNS-VS). Adults aged 18–65 years, who were 1–12-months post-mild TBI and experienced cognitive impairment, were randomly assigned to receive either MLC901 two capsules (0.4g/capsule) or placebo three times a day for 6 months using centralized stratified permuted block randomization. Secondary outcomes: Rivermead Post-Concussion Symptoms Questionnaire (RPQ; neurobehavioral sequelae); Health Related Quality of Life (QOLIBRI); Hospital Anxiety and Depression Scale (HADS); and safety. Mixed effects models of repeated measures with intention to treat analysis were employed. A Least Square Mean Difference (LSMD) from baseline to 3-, 6-, and 9-month follow-up was calculated with 95% confidence intervals (CI). Results In the analysis, 182 participants (47.8% females) were included. Multivariable mixed effects model analysis did not reveal significant improvements in complex attention (LSMD = −1.18 [95% CI −5.40; 3.03; p = 0.58]) and other cognitive domains at 6 months in the MLC901 group compared to the Placebo group. There were significant improvements in RPQ, QOLIBRI, anxiety and depression in the MLC901 group compared to the Placebo group at 6 and 9 months (LSMD −4.36 [−6.46; −2.26] and −4.07 [−6.22; −1.92], 4.84 [1.58; 8.10] and 3.74 [0.44; 7.03], −1.50 [−2.29; −0.71 and −0.96 [−1.84; −0.08], −1.14 [−1.92; −0.35] and −1.14 [−1.94; −0.34]), respectively. MLC901 tested was proven safe. Conclusions Although the 6-month treatment with MLC901 did not result in a statistically significant difference with placebo for CNS-VS measurement of cognitive domains in individuals with mild TBI, the study showed a clinically and statistically significant improvement in all clinical scales assessed by the investigators.
Keywords: General Science & Technology; Traumatic brain injury; Quality of life; Cognitive impairment